1989
DOI: 10.1007/bf01578751
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral 5-hydroxytryptophan administration on feeding behavior in obese adult female subjects

Abstract: Nineteen obese female subjects with body mass index ranging between 30 and 40 were included in a double-blind crossover study aimed at evaluating the effects of oral 5-hydroxytryptophan administration on feeding behavior, mood state and weight loss. Either 5-hydroxytryptophan (8 mg/kg/day) or placebo was administered for five weeks during which patients were not prescribed any dietary restrictions. Feeding behavior was investigated by means of a questionnaire designed to establish the onset of anorexia and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…This is indirectly supported by our previously reported data showing that the oral administration of 5-HTP in obese patients is effective in reducing energy intake by predominantly inhibiting carbohydrate intake, and therefore improving patients' compliance to low energy dietary prescriptions. 13,14 On the other hand, the evidence obtained in the present study that patients' eating behaviour complied well with standard nutritional advice (50% of energy intake from carbohydrates, 30% from fats and 20% from proteins) despite a reduction in predicted brain tryptophan concentrations, might reason against a selective role for brain serotonin in modulating macronutrient selection. However, it must be remembered that in the present study, patients had a history of diabetes dating at least 3 years.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…This is indirectly supported by our previously reported data showing that the oral administration of 5-HTP in obese patients is effective in reducing energy intake by predominantly inhibiting carbohydrate intake, and therefore improving patients' compliance to low energy dietary prescriptions. 13,14 On the other hand, the evidence obtained in the present study that patients' eating behaviour complied well with standard nutritional advice (50% of energy intake from carbohydrates, 30% from fats and 20% from proteins) despite a reduction in predicted brain tryptophan concentrations, might reason against a selective role for brain serotonin in modulating macronutrient selection. However, it must be remembered that in the present study, patients had a history of diabetes dating at least 3 years.…”
Section: Discussionmentioning
confidence: 41%
“…Also, patients were questioned for the presence of side effects, including nausea and vomiting, using a previously validated questionnaire. 13,14 To test patients' compliance to treatment 24 h urinary excretion of 5-hydroxy-indoleacetic acid (5-HIAA) was also determined on day 0, day 7 and day 14, using the chromatographic-colorimetric method described by Udenfriend et al 22 Data obtained in the study group were then compared to those simultaneously obtained in a control group of 18 gender-and age-comparable healthy subjects. Blood samples were obtained and processed as described for diabetic patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Previous observations have shown that oral administration of 5-hydroxytryptophan (5-HTP) is useful for losing weight. [27][28][29] Moreover, it has been shown that 5-HTP increases plasma concentration of leptin, the hormone synthesized from fat that inhibits the feeling of hunger in the hypothalamus. [30][31][32][33] Currently, 5-HTP is available exclusively in oral or parenteral formulations.…”
Section: Introductionmentioning
confidence: 99%